Parallel computation : models and methods - Akl, Selim G. (Prentice Hall, 1997)
An understanding of the role of parallel algorithms and the technical knowledge for designing and analyzing them are essential to anyone entering the field of parallel computation. Familiarity with the models associated with the algorithms is also essential. Thus, focusing on "models and methods," author Selim G. Alk presents the following areas of parallel computation: an overview of the models, including combinational circuits, interconnection networks, shared memory machines, and models that use buses; an overview of the methods, including prefix computation, list ranking, divide and conquer, split and plan, matrix multiplication, broadcasting with selective reduction, and many others; and a wide variety of computational problems, which illustrate and contrast the models and methods. Examples include sorting, searching, and numerical problems; combinatorial problems; and problems in graph theory and computational geometry.